2004
DOI: 10.1023/b:johe.0000025327.70959.d3
|View full text |Cite
|
Sign up to set email alerts
|

Home Deliveries in Indonesia: Who Provides Assistance?

Abstract: Indonesia has set an ambitious target of reducing its maternal mortality rate to 125 maternal deaths per 100,000 live births by the year 2010. This poses formidable challenges in a geographically diverse country where the majority of births occur at home. One option for the Indonesian government in order to reduce its maternal mortality would be to increase rates of skilled assistance for home deliveries. In order to design appropriate policies to achieve this, it is imperative to understand the determinants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…16,17 The Afghan Ministry of Public Health has been promoting health care for the poor, and evidence from other studies has shown success in providing outpatient services to the poor in Afghanistan. 13 However, we found that use of skilled birth attendants was highly inequitable in Afghanistan, with the poor being at a stark disadvantage.…”
Section: Determinants Of Skilled Birth Attendant Usementioning
confidence: 99%
“…16,17 The Afghan Ministry of Public Health has been promoting health care for the poor, and evidence from other studies has shown success in providing outpatient services to the poor in Afghanistan. 13 However, we found that use of skilled birth attendants was highly inequitable in Afghanistan, with the poor being at a stark disadvantage.…”
Section: Determinants Of Skilled Birth Attendant Usementioning
confidence: 99%
“…Key aspects of safe delivery practices include the physical setting, availability of supplies and equipment, level of skill and selfconfidence of the provider and a supportive environment. 10 While the constraints faced by women living in developing countries in accessing professional birthing care and quality of care issues are well researched, [11][12][13][14][15] the views and experiences of skilled attendants assisting childbirth in women's homes have not been available. This paper examines the experiences of skilled birth attendants carrying out home-based deliveries in a rural setting in Bangladesh, in comparison with deliveries attended by the same attendants in health facilities.…”
mentioning
confidence: 99%
“…The underlying social causes of maternal mortality in Indonesia include early marriage, limited resources and incapability of the infrastructure (Beegle et al 2001;Thind and Banerjee 2004). The common medical causes of maternal mortality include postpartum hemorrhage, eclampsia, abortion complications, infections and prolonged labor (Beegle et al 2001;Thind and Banerjee 2004). There is widespread evidence that most Indonesian women still sought the services of traditional birth attendants (TBAs) and home delivery is still predominant, especially in rural areas (Thind and Banerjee 2004).…”
Section: Background On Prenatal Care In Indonesiamentioning
confidence: 99%
“…The common medical causes of maternal mortality include postpartum hemorrhage, eclampsia, abortion complications, infections and prolonged labor (Beegle et al 2001;Thind and Banerjee 2004). There is widespread evidence that most Indonesian women still sought the services of traditional birth attendants (TBAs) and home delivery is still predominant, especially in rural areas (Thind and Banerjee 2004). However, home deliveries by traditional birth attendants (TBAs) can lead to untreated obstetric complications (e.g., prolonged labor, excessive bleeding, fever, anemia, ruptured uterus, and maternal convulsions) especially if the mothers are not able to obtain the necessary higher level care when complications arise (Thind and Banerjee 2004).…”
Section: Background On Prenatal Care In Indonesiamentioning
confidence: 99%